THE FREQUENCY OF SARCOPENIA IN OLDER AGE GROUPS: EVALUATION OF DIAGNOSTIC CRITERIA - Yu. A. Safonova; E. G. Zotkin (Научно-практическая ревматология)
The prevalence of sarcopenia in different countries of the world has been well studied. However, the criteria of different international professional groups are used to diagnose the disease, which leads to large variability in data on the frequency of sarcopenia in the population. The paper presents the results of studying the frequency of sarcopenia, by using the diagnostic criteria of different working groups. The measures characterizing muscle strength and skeletal muscle function were analyzed; the components that are most important for the diagnosis of sarcopenia were identified in the studied patient group.Objective: to determine the detection rates of sarcopenia among people aged over 65 years in accordance with the guidelines of different international professional groups and to identify the most significant component for its diagnosis.Subjects and methods. The investigation enrolled 230 people older than 65 years (mean age, 74.0±6.5 years) who were followed up in an outpatient setting. Sarcopenia was diagnosed according to the 2010 European Working Group on Sarcopenia in Older People (EWGSOP) criteria. To confirm its diagnosis, the appendicular muscle mass index (AMMI) was calculated using dual-energy X-ray absorptiometry (DXA) on a HOLOGIC QDR Explorer; muscle strength was measured with a Jamar-J00105 handheld dynamometer (Sammons Preston Inc., USA). Muscle function was also examined using the short physical performance battery (SPPB). The frequency of sarcopenia diagnosed by the criteria of the International Working Group on Sarcopenia (IWGS), the Foundation for the National Institutes ofHealth (FNIH), and EWGSOP were comparatively analyzed. Results and discussion. The frequency of sarcopenia in the sample of people aged over 65 years was the same when using the diagnostic EWGSOP and IWGS criteria (30%) and was significantly higher than when applying the FNIN criteria (19.8%). The frequency of sarcopenia increased from 21.4% at the age of 65–74 years to 52.9% at the age of over 85 years according to the EWGSOP and IWGS criteria and from 16.2% to 29.4%, respectively, by the FNIN criteria. Dynamometry showed that the muscle strength was significantly lower in patients with low muscle mass than in those with normal muscle mass (the average mass was 15.1±5.4 and 18.2±5.4 kg, respectively; p<0.001) among both males and females. The average SPPB scores in the entire sample were low in all the studied groups (7.6±3.1). It was significantly lower in patients with low muscle mass than in people with normal muscle mass (6.9 and 7.9 scores, respectively; p=0.016) as shown mainly by the Tandem test (p=0.0002). No substantial differences in the frequency of sarcopenia were found in different age groups according to the EWGSOP and EWGSOP2 criteria.Conclusion. The frequency of sarcopenia among people aged over 65 years according to the criteria adopted by professional communities varied widely from 19.8% (FNIN) to 26.5% (EWGSOP2) and 30% (EWGSOP). With age, the frequency of sarcopenia increased, reaching 52.9% among people over 85 years of age. Muscle strength measurement versus other functional tests is a more sensitive diagnostic method for sarcopenia.